Management of Long-Term Sores and Ulcers of Breast Cancer Survivors With Chinese Herbal Medicines: A Case Report - Zhang, Yuanfeng; Zhang, Bing; Zhou, Weilong; Lu, Tao (Frontiers in Psychiatry, 2022)
Background The treatment of long-term sores and ulcers of breast cancer metastatic recurrence is a serious challenge with successful cases rarely being documented. Herein we reported a successful case using the internal vitality supporting method of Chinese herbal medicine (CHM). Case Summary A 59-year-old female Chinese patient, 10 years after breast cancer surgery, developed metastatic lesions in the lung. Thereafter she received radiofrequency ablation and adjuvant treatments for 1 year with severe sequelae, a right unhealed sore and ulcer. She became frustrated and depressive. And subsequently sought exclusive treatment under the guidance of a Traditional Chinese Medicine (TCM) physician. The patient's condition was categorized as a Qi (or vitality) deficiency-related sore and ulcer. In the next six months, the patient still follows a traditional Chinese medicine therapeutic regimen based on the internal vitality supporting method of Chinese herbs. Conclusion The sore and ulcer from the surgical wound were healed. Up to now, the tumor markers have remained stable. TCM personalized survivorship treatment and psychosocial support can help patients improve their quality of life after acute treatment and in the long-term for cancer survivors.